Exploring Ethnoscience-Oriented PjBL-STEM Model Implementation in Biology Education: A Traditional Food Context Study - Julianti, Maritza; Aina, Tiara; Prasiwi, Jesita; Fatonatullaillah, Indah; Widiyastuti, Winda; Usman, Usman (International Journal of STEM Education for Sustainability, 2025)
This study set out to investigate the application of the ethnoscience-focused PjBL-STEM model in biology education.  By examining traditional meals as part of local wisdom, this methodology focuses on ethnoscientific values.  A descriptive qualitative method incorporating literature review approaches was employed to investigate the idea, application, and future possibilities of this model.  The study's findings suggest that PjBL, STEM, and ethnoscience can be combined to enhance the relevance, context, and cultural richness of education.  Additionally, it has been demonstrated that this model fosters the growth of 21st-century abilities including critical thinking, creativity, communication, and teamwork as well as greater scientific literacy and learning motivation. Teachers serve as a link between local knowledge and contemporary science. Therefore, theethnoscience-oriented PjBL-STEM model can be an effective approach in realizing contextual, applied, and culturally rooted biology education.